Evaluasi Program Penyediaan Prasarana Sarana Utilitas Perumahan Di Kota Serang (Studi Kasus Perumahan Bumi Agung Permai II dan Perumahan Sukawana Asri) - Dadan Priatna; Leo Agustino; Arenawati (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
This research focuses on the Evaluation of the Housing Utility Infrastructure Provision Program in Serang City (Case Study of Bumi Agung Permai II Housing and Sukawana Asri Housing). The aim of the study was to find out the results of the Evaluation of the Housing Facilities and Utilities Infrastructure Provision Program in Serang City. Evaluation from William Dunn (2008:429), namely effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. The research method used is descriptive qualitative method. Test the validity of the data using source and triangulation techniques member check. Data analysis used Miles and Huberman's qualitative data analysis. The research results are known (1). The effectiveness of the PSU program is still not optimal, which is marked by the fact that it is not in accordance with the work plan. (2). Efficiency is still weak due to the minimal PSU budget. (3). Adequacy is still minimal, there are damaged access roads, measuring devices are not available (drone), minimal institutional cooperation. (4). Alignment is still less than optimal. (5). Weak responsiveness is characterized by the lack of friendliness of Serang City Disperkim employee services. (6). Less optimal accuracy is characterized by the absence of children's playground facilities in Sukawana Asri housing.